Regression of lipoedematous scalp following cryolipolysis using an icepack, with a novel dermoscopic feature of yellow background. (12th October 2021) - Kharkar, V.; Vishwanath, T.; Kamble, P.
Abstract : The novel use of cryolipolysis via icepacks, a readily available and inexpensive device, is described for lipoedematous scalp with subjective and objective relief. This is a simple solution to a troublesome, intractable condition and may readily be utilized for patient benefit. Juxtaposing pre and post clinical images